To Wrap or Not? Utility of Anti-reflux Procedure in Infants Needing Gastrostomy Tubes - Khan, Faraz A.; Nestor, Kelsey; Hashmi, Asra; Islam, Saleem (Frontiers in Pediatrics, 2022)
Purpose: Gastrostomy tube (GT) insertion is commonly performed in children with failure to thrive. Pediatric patients’ frequently have gastroesophageal reflux (GER) and discerning pathological GER can be challenging. Moreover, there is some evidence that GT insertion may lead to worsening GER and to avoid a subsequent anti-reflux procedure (ARP), though controversial some surgeons advocate considering an ARP concomitantly. The purpose of this report is to assess outcomes in infants who underwent a GT vs. GT with ARP. Methods: Retrospective review of all infants who had a GT placed at a single institution from 2009-2014. The patients were then divided into two cohorts based on the index operation i.e. GT vs GT with ARP and outcomes compared. Results: 226 operations (104 GT, 122 GT with ARP) were performed. The cohorts were similar in gender, gestational age, race, weight, median age, LOS, and proportion of neurologically impaired patients. Preoperative GER was significantly higher in the GT with ARP cohort (91% vs. 18%). No difference in the rate of immediate complications was noted between the two groups. Postoperative increase in anti-reflux medications was significantly higher in the GT cohort (p=0.01). Post-op GER needing a secondary procedure (ARP or GJ tube) was noted in 21/104 (20%) patients. Those needing an additional procedure vs. those with GT alone were similar in the proportion of patients with pre-op GER, neurologic impairment, type of feeds, and age. Conclusion: Identifying patients who would benefit from a concomitant ARP remains challenging. A fifth of GT patients needed a subsequent procedure despite most high-risk patients having already undergone an ARP. Since the overall rate of complications remained similar, initial GT approach can be considered reasonable.